IS/IT STRATEGIC PLANNING USING WARD & PEPPARD METHOD (CASE STUDY : STIKES BINA CIPTA HUSADA) - Siti Nur Amalia; Wahyu Adi Prabowo (JURNAL TEKNOLOGI INFORMASI DAN KOMUNIKASI, 2023)
STIKes Bina Cipta Husada (STIKes BCH) in its business operations has used information systems and information technology. However, the existing information system is still not integrated between one unit and another, causing data redundancy and slow operational processes. Strategic planning of IS/IT is needed to support strategic activities in STIKes BCH, because the lack of planning in the use and development of IS/IT can also impede the organization in achieving its goals and objectives. Therefore, this research focuses on Strategic Planning of IS/IT, which aims to use the output of this research as a reference for the 5-year strategic plan of IS/IT and improve the competitiveness in the education institution competition. The Ward & Peppard method was chosen in the process of IS/IT strategic planning because it has the advantage of relatively complete analysis tools, not only focusing on IS/IT conditions, but also considering internal and external business conditions and IS/IT management. The tools used to formulate the IS/IT strategy include SWOT, Value Chain, PEST, Porter's Five Force, McFarlan's Strategic Grid, and CSF. The result of this research is the IS Business Strategy, IT Strategy, and IS/IT Management Strategy that can be implemented in STIKes BCH.